Writing task complexity, students’ motivational beliefs, anxiety and their writing production in English as a second language - Rahimi, Muhammad; Zhang, Lawrence Jun (Reading & writing, 2019)
This study explored the effects of increasing the number of elements and the degree of reasoning on second language (L2) writing and also examined the relationship between writing motivational beliefs and anxiety and L2 writing in simple versus complex tasks. Sixty upper-intermediate L2 learners were invited to write simple and complex argumentative essays and to complete a multidimensional writing motivational beliefs questionnaire and a writing anxiety questionnaire. Multiple measures were taken to detect the effects of increasing task complexity on learners’ L2 writing syntactic complexity and accuracy and the relationship between individual learner factors and each of the L2 writing measures in the simple and complex task. Results show that increasing task complexity result in increases in subordination use and simultaneous decreases in learners’ L2 writing accuracy. The role of motivation and anxiety is more evident in the complex task. These results are discussed with reference to the Cognition Hypothesis and the Trade-off Hypothesis, highlighting the necessity of employing multidimensional measures of motivation and anxiety.